Gray-cheeked Thrush (Catharus minimus minimus) distribution and habitat use in a montane forest landscape of western Newfoundland, Canada - Darroch M. Whitaker; Philip D. Taylor; Ian G. Warkentin (Avian Conservation and Ecology, 2015)
Once abundant, the Newfoundland Gray-cheeked Thrush (Catharus minimus minimus) has declined by as much as 95% since 1975. Underlying cause(s) of this population collapse are not known, although hypotheses include loss of winter habitat and the introduction of red squirrels (Tamiasciurus hudsonicus) to Newfoundland. Uncertainties regarding habitat needs are also extensive, and these knowledge gaps are an impediment to conservation. We investigated neighborhood (i.e., within 115 m [4.1 ha]) and landscape scale (i.e., within 1250 m [490.8 ha]) habitat associations of Gray-cheeked Thrush in a 200-km² study area in the Long Range Mountains of western Newfoundland, where elevations range from 300-600 m and landcover was a matrix of old growth fir forest, 6- to 8-year-old clearcuts, coniferous scrub, bogs, and barrens. Thrushes were restricted to elevations above ~375 m, and occurrence was strongly positively related to elevation. Occurrence was also positively related to cover of tall scrub forest at the neighborhood scale, and at the landscape scale showed curvilinear relations with the proportion of both tall scrub and old growth forest that peaked with intermediate amounts of cover. Occurrence of thrushes was also highest when clearcuts made up 60%-70% of neighborhood landcover, but was negatively related to cover of clearcuts in the broader landscape. Finally, occurrence was highest in areas having 50% cover of partially harvested forest (strip cuts or row cuts) at the neighborhood scale, but because this treatment was limited to one small portion of the study area, this finding may be spurious. Taken together, our results suggest selection for mixed habitats and sensitivity to both neighborhood and landscape-scale habitat. More research is needed on responses of thrushes to forestry, including use of older clearcuts, partially harvested stands, and precommercially thinned clearcuts. Finally, restriction of thrushes to higher elevations is consistent with the hypothesis that they have been impacted by squirrels, because squirrels were rare or absent at these elevations.